2011
DOI: 10.4314/tjpr.v10i5.17
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal Activity of &#945,&#946-Unsaturated &#948-Lactones: Promising Compounds for the Development of New Therapeutic Alternatives

Abstract: The parasite resistance and side effects of drugs used to treat protozoal diseases have led to the search for new therapies, both natural and synthetic. Studies have shown that various α,β-unsaturated δ-lactones displayed high antiprotozoal activity and thus are promising compounds for new drug discovery and development. These compounds and their activity are examined in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the early phases of drug discovery, computer‐aided techniques have often been used to discover and optimize novel hit or lead compounds of pharmaceutical interest [42] . Aligned to our in silico prediction results, the specialized literature indicated that some natural lactones displayed anti‐ Plasmodium falciparum effect, [24] and α,β‐unsaturated lactones presented antiprotozoal activity [43] . Following our in silico results, we investigated in vitro trypanocidal activities of (+)‐phomalactone ( 1 ), hydroxypestalopyrone ( 2 ), and pestalopyrone ( 3 ) against T. cruzi epimastigotes and trypomastigotes aiming to determine their inhibition activities (IC 50 ).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In the early phases of drug discovery, computer‐aided techniques have often been used to discover and optimize novel hit or lead compounds of pharmaceutical interest [42] . Aligned to our in silico prediction results, the specialized literature indicated that some natural lactones displayed anti‐ Plasmodium falciparum effect, [24] and α,β‐unsaturated lactones presented antiprotozoal activity [43] . Following our in silico results, we investigated in vitro trypanocidal activities of (+)‐phomalactone ( 1 ), hydroxypestalopyrone ( 2 ), and pestalopyrone ( 3 ) against T. cruzi epimastigotes and trypomastigotes aiming to determine their inhibition activities (IC 50 ).…”
Section: Resultsmentioning
confidence: 75%
“…[42] Aligned to our in silico prediction results, the specialized literature indicated that some natural lactones displayed anti-Plasmodium falciparum effect, [24] and α,β-unsaturated lactones presented antiprotozoal activity. [43] Following our in silico results, we investigated in vitro trypanocidal activities of (+)-phomalactone (1), hydroxypestalopyrone (2), and pestalopyrone (3) against T. cruzi epimastigotes and trypomastigotes aiming to determine their inhibition activities (IC 50 ). Cytotoxicity assays toward Vero cells (CC 50 ) and selectivity index (SI, CC 50 /IC 50 ) values were also determined (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…γ-Decalactone and lactone analogs have been shown to be effective against Aspergillus species, C. albicans, Penicillium roqueforti, and Staphylococcus aureus, , Erwinia amylovora and Pantoae agglomerans, and even against protozoa . Effective antimicrobial volatiles include lipoxygenase pathway products against Alternaria alternata and Botrytis cinerea and against Colletotrichum acutatum .…”
Section: Introductionmentioning
confidence: 99%